BS IEC 62873-3-3 AMD1. Residual current operated circuit-breakers for household and similar use. Part 3-3. Specific requirements for RCDs with screw-type terminals for external untreated aluminium conductors and with aluminium screw-type terminals for use with copper or with aluminium conductors (3rd December 2020) - British Standards Institution,
No abstract available